Proposed new interior design of Cosry Boutique for Cosry Boutique Wise Sdn.Shd. at 36723(No. 80) Jalan Raja Permaisuri Bainun (Jalan Kampar), Ipoh, Perak / Azuarniza Awang - Awang, Azuarniza (Faculty of Architecture, Planning and Surveying, 2011)
This report is produce based on the final years student's project requirement. The student report must align with the proposal which is to propose a new design scheme for Cosry Boutique for Cosry Boutique Wise Sdn Bhd at Lot 36723(No 80) Jalan Raja Permaisuri Bainun (Jalan Kampar), Ipoh Perak and to develop a design scheme that would show the true colors of traditional elegance in its interior design. The research also will give the student new vital knowledge in order to develop new design scheme and solve existing problem. It is challenge to design a boutique which tries to explore new method in displaying luxury items such as clothing and accessories to enhance that natural beauty to extraordinary. This project offers a comprehensive range of facilities and space according to the guidelines set up by client. A series of interview and observation has been conducted in order to collect relevant data and information. Base on case study and observation, it can be concluded that it is important to create and design a wedding boutique space which fulfils the clients’ requirements and adapting appropriate design concept and schemes in order to enhance the success of the brand itself. Besides that, it is also essential for the boutique to be a space that is compelling and inviting because the main point of the boutique itself is to sell. The finding of this research shows that the Cosry Boutique needs a strong and vibrant character in order for it to be successful as not only for its artistic and glamorous designs but also for its high level of customer services and has caught the attention of many high profile and affluent clientele around South East Asia. Choosing the right site is also important in making certain that the project is successful. The location is situated at Lot 36723 (No 80) Jalan Raja Permaisuri Bainun (Jalan Kampar) Ipoh Perak. The location is strategic for the boutique. It is a special unit of lot which located at Ipoh one was chosen due to its marketability and located in the heart of Ipoh. Situated in many public activities also adds point to this proposed site. Other than that, choosing a suitable design concept and image needs to be able to be highly blended together for it to work with colours. Hopefully, one day Cosry Boutique will be in the hearts of fashion lovers all thought out Malaysia beating other coveted brands available here.